Battery-grade doped modified manganese ferric sodium pyrophosphate positive electrode material, and preparation method and application of battery-grade doped modified manganese ferric sodium pyrophosphate positive electrode material
By using ion exchange method and secondary sintering process on the basis of the precursor of ferroferric phosphate, nitrogen-doped carbon-coated sodium manganese phosphate phosphate positive electrode material was prepared, which solved the problems of uneven distribution of dopant and the influence of sulfur impurities, and significantly improved the electrochemical performance and cyclic stability of the material.
Patent Information
- Application Number
- CN202411993556.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, when preparing the positive electrode material of sodium manganese pyrophosphate, it is difficult to ensure uniform distribution and precise regulation of dopants in the body phase of the material, resulting in poor electrochemical performance and the presence of sulfur impurities affects the cycle stability.
The iron method and ion exchange method are used to prepare the precursor of ferromanteam phosphate, and the nitrogen-doped carbon film is uniformly coated on the surface of sodium manganteam pyrophosphate particles through secondary sintering process to control the sulfur impurity content and ensure that the doped metal elements are uniformly distributed in the precursor lattice.
The structural stability, specific capacity, rate performance and cycle stability of the positive electrode material of ferromanganese pyrophosphate are improved, the free carbon content is reduced, manganese dissolution and Jahn-Teller effect are suppressed, and the electrochemical performance and compaction density of the material are optimized.
Smart Images

Figure CN119706773A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of battery materials, and in particular relates to a battery-grade doped modified sodium manganese iron phosphate pyrophosphate positive electrode material and a preparation method and application thereof. Background Art
[0002] Green and sustainable energy storage technology is the top priority to solve the contemporary environmental pollution, climate change, and energy crisis caused by traditional fossil fuels. Although lithium-ion batteries are widely used in electric vehicles, large-scale energy storage, and 3C products as secondary energy storage power sources with high energy density, long cycle stability, and high safety, the limited crustal abundance and high cost of lithium resources have greatly restricted their long-term development. On the contrary, the high crustal abundance and low cost of sodium resources have made sodium-ion batteries with similar working principles to lithium-ion batteries a new type of industrial energy storage device. Sodium-ion battery positive electrode materials can be divided into three types: transition metal oxide type, Prussian blue type, and polyanion type. Among them, iron-based polyanion sodium-ion battery positive electrode materials have become a hot spot in industrial research due to their low cost, environmental friendliness, high structural stability, and high thermal stability.
[0003] Sodium iron phosphate pyrophosphate (Na4Fe3(PO4)2P2O7, NFPP) is a mixed iron phosphate with the characteristics of low cost, high stability and high safety. However, its low voltage platform (3.0V) and low specific capacity bottleneck cannot meet the demand for high energy density sodium ion battery cathode materials. Olivine-type sodium iron manganese phosphate pyrophosphate is a mixed manganese iron phosphate. It forms a solid solution phase by replacing iron atoms in the bulk phase with manganese atoms. It has the advantages of three-dimensional sodium ion transport channels, a higher voltage platform (3.7V), high safety and high energy density. It is expected to become a new generation of high energy density sodium ion battery cathode material. Due to the introduction of manganese atoms, it is limited by low intrinsic electronic conductivity, slow electrochemical kinetics, Jahn-Teller effect caused by manganese dissolution, poor cycle stability and rate performance. Researchers are committed to modifying sodium iron manganese phosphate pyrophosphate from the aspects of carbon coating, nano-sizing, and cation doping. However, the existing doping modification technology is based on the subsequent addition of dopants, manganese sources, iron sources, etc., followed by mixing and sintering. It cannot ensure the uniform distribution of various atoms in the bulk phase of sodium manganese iron pyrophosphate and accurately control the electronic structure and stability of the material, thereby affecting the electrochemical performance. The existing technology has not yet deeply explored the negative effects of sulfur impurities in the synthesized sodium ion battery positive electrode material on the electrical performance.
[0004] In addition, the conventional spray sintering carbon coating method in the prior art cannot ensure that the carbon layer is completely and evenly coated on the surface of the sodium ferromanganese phosphate pyrophosphate primary particles, so that some of the sodium ferromanganese phosphate pyrophosphate primary particles are not coated with the carbon layer and have poor conductivity, and are directly in contact with the electrolyte, which aggravates manganese dissolution and HF etching, affects the structural stability of the material, and further increases the internal resistance of the sodium ion battery and deteriorates the cycle stability performance; in addition, part of the carbon source is separated from the sodium ferromanganese phosphate pyrophosphate particles in the form of free carbon, and the conductivity of the material deteriorates. Summary of the invention
[0005] In order to solve the problems existing in the above-mentioned prior art, the primary purpose of the present invention is to provide a preparation method of sodium ferromanganese phosphate pyrophosphate.
[0006] Another object of the present invention is to provide a kind of sodium ferromanganese phosphate pyrophosphate.
[0007] Another object of the present invention is to provide the use of the above-mentioned sodium ferromanganese phosphate pyrophosphate in the preparation of sodium ion batteries.
[0008] In order to achieve the above object, the present invention provides the following technical solutions:
[0009] A method for preparing sodium ferromanganese phosphate pyrophosphate comprises the following steps:
[0010] S1. The elemental iron is placed in phosphoric acid for reaction, an oxidant is added for reaction, and an alkaline pH regulator containing nitrogen is added to obtain a first system containing ammonium iron phosphate;
[0011] S2. mixing manganese sulfate and a doping metal salt, adding the mixture to a first system containing ammonium ferric phosphate, adjusting the pH value of the system to 6.8 to 11, and reacting the mixture under an inert atmosphere to obtain a first precursor;
[0012] S3. The first precursor is mixed with a sodium source, a phosphorus source, and a carbon source, ground, spray dried, and sintered in an inert atmosphere to obtain a first sintered material;
[0013] S4. The first sintered material is secondarily sintered in a mixed atmosphere of an inert gas and a gaseous nitrogen source to obtain the sodium ferromanganese phosphate pyrophosphate.
[0014] The present invention prepares an ammonium ferric manganese phosphate precursor based on an iron process and an ion exchange method, and prepares it into a secondary coated nitrogen-doped carbon-coated sodium ferric manganese phosphate pyrophosphate. The preparation method of the present invention can control the sulfur impurity content in the precursor, avoid a secondary desulfurization process, and make the sulfur impurity content (≤100ppm) in the first precursor modified ammonium ferric manganese phosphate reach the battery level, thereby improving the cycle performance of the sodium ion battery.
[0015] The present invention adopts an ion exchange method to prepare a low-sulfur impurity ammonium manganese iron phosphate precursor, wherein the total molar amount of manganese, iron, and doped metals to the molar amount of phosphorus source is less than 1, which greatly improves the tap density of the precursor, facilitates the construction of iron / manganese site defects when preparing sodium manganese iron phosphate pyrophosphate, and improves the sodium storage capacity of the positive electrode material. The doped metal elements are evenly distributed at the atomic level in the precursor lattice, effectively regulating the internal crystal electronic structure of sodium manganese iron phosphate pyrophosphate, improving the structural stability of sodium manganese iron phosphate pyrophosphate, and at the same time alleviating the volume expansion effect of sodium ions during the embedding / de-embedding process, thereby improving the electrochemical performance of the positive electrode material.
[0016] The present invention uses a secondary sintering process to uniformly coat the surface of sodium manganese iron phosphate pyrophosphate particles with a nitrogen-doped carbon film. Nitrogen atoms, as doping atoms (pyrrolic nitrogen, pyridinic nitrogen) in the carbon film, have electron affinity, can provide lone pairs of electrons and contribute free electrons, regulate the local charge distribution and electron cloud structure in the carbon film, improve the electronic conductivity of the material, and improve the wettability of the electrolyte on the surface of the material. Nitrogen-doped carbon can construct defect sites, provide more sodium ion transmission paths and storage space for the sodium manganese iron phosphate pyrophosphate active material, and thus improve the specific capacity, rate performance and cycle stability of the positive electrode material. The secondary sintering process can reduce the content of free carbon in the finished material after pulverization, effectively regulate the uniformity and density of the carbon coating layer in the material, and thus improve the conductivity and structural stability of the material, further suppress the Jahn-Teller effect caused by manganese dissolution, and optimize the crystallinity of the sodium manganese iron phosphate pyrophosphate particles, thereby improving the electrochemical properties and compaction density of the material.
[0017] In the first system of the present invention, elemental iron reacts with phosphoric acid to generate ferrous dihydrogen phosphate, and then an oxidant is added to convert it into ferric phosphate, and then the first system containing ammonium ferric phosphate is obtained after aging and adjusting the pH. The present invention adds a mixed solution of a manganese source and a dopant to the first system, and prepares an ammonium ferric manganese phosphate precursor with low sulfur impurities by an ion exchange method. Through adsorption, complexation and other mechanisms, ion exchange reactions are carried out with manganese salts and doped metal salts to exchange the iron element in the ammonium ferric phosphate, thereby forming metal-doped ammonium ferric manganese phosphate. Since ferrous dihydrogen phosphate is oxidized to ferric phosphate to produce phosphate radicals, the exchanged iron ions continue to react with manganese ions, doped metal ions and phosphate radicals in the system to form metal-doped ammonium ferric manganese phosphate.
[0018] Specifically, the chemical formula of the sodium manganese iron pyrophosphate is Na4Mn α Fe 3-α-β M β (PO4)2P2O7, 0<α<3, 0<β<0.3, M is the doping metal.
[0019] Preferably, 1<α<2, 0.1<β<0.2.
[0020] Specifically, the molar ratio of the elemental iron to the phosphoric acid is 1:(2-5).
[0021] Specifically, in step S1, the reaction time of elemental iron and phosphoric acid is 0.5 to 6 hours.
[0022] Specifically, the temperature for the reaction of elemental iron and phosphoric acid in step S1 is 20-50°C.
[0023] Specifically, in the first system, after the oxidant is added, the reaction temperature is 50 to 85° C. and the reaction time is 1 to 20 hours.
[0024] Specifically, the oxidant is at least one of hydrogen peroxide, oxygen and ozone.
[0025] Specifically, the pH regulator containing nitrogen element is at least one of ammonia water, urea or ammonium carbonate.
[0026] The pH regulator in the present invention is required to be alkaline, be able to generate ammonium ions with phosphoric acid, and not introduce other impurity ions.
[0027] Specifically, the pH value of the first system after oxidation is adjusted to 6.8-11.
[0028] Specifically, the doping metal is at least one of Al, Ti, V, Ca, Ce, Cu, Cr, Zr, Sr, Ni, Co, Zn, Sn, Nb, Na, Mo, Mg, W, and La.
[0029] Specifically, the doping metal salt may be at least one of sulfate, nitrate, acetate, oxalate or chloride of the corresponding metal ion.
[0030] Specifically, the ratio of the total molar number of manganese, iron and doping metal to the molar number of phosphorus in the first precursor is less than 1.
[0031] Specifically, the reaction temperature in step S2 is 50-85°C.
[0032] Specifically, the reaction time in step S2 is 1 to 20 hours.
[0033] Specifically, in step S3, the ratio of the molar amount of Na, the total molar amount of metals in the first precursor, and the molar amount of P is (3.8-4.6):3:(3.8-4.6).
[0034] Specifically, in step S3, the carbon source is 0.05-5 wt % of the mass of the first precursor.
[0035] Preferably, in step S3, the carbon source is 2-4 wt% of the mass of the first precursor.
[0036] Specifically, the sodium source is any one or more sodium sources known in the art for preparing positive electrode active materials, for example, it can be at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide, disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium citrate, sodium pyrophosphate, sodium phosphate, sodium nitrate, sodium chloride, and sodium oxalate.
[0037] Specifically, the phosphorus source is any one or more phosphorus sources known in the art for preparing positive electrode active materials, for example, it can be at least one of diammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, sodium pyrophosphate, ammonium hypophosphite, ammonium polyphosphate, sodium phosphite, sodium metaphosphate, and sodium tripolyphosphate.
[0038] Specifically, the carbon source is any one or more carbon sources known in the art for preparing positive electrode active materials, for example, it can be at least one of glucose, sucrose, starch, cellulose, polyethylene glycol, fructose, ascorbic acid, polyvinyl pyrrolidone, and polyvinylidene fluoride.
[0039] Specifically, the sintering in step S3 is to heat the temperature to 350-450° C. at a heating rate of 1-20° C. / min, keep the temperature for 1-8 hours, and then heat the temperature to 500-650° C. at a heating rate of 1-20° C. / min, and keep the temperature for 2-20 hours.
[0040] Specifically, the nitrogen source is at least one of urea, dicyandiamide, melamine, thiourea and monocyanamide.
[0041] Nitrogen atoms and carbon atoms have similar atomic radii. Nitrogen atoms as doping atoms in carbon films (pyrrolic nitrogen, pyridinic nitrogen) have better electron affinity, can provide lone pairs of electrons and contribute free electrons, regulate the local charge distribution and electron cloud structure in the carbon film, improve the electronic conductivity of the material and the wettability of the electrolyte on the surface of the material, and promote the transmission of electrons and sodium ions; at the same time, nitrogen atom doping can construct defect sites, providing more sodium ion transmission paths and storage space for the sodium manganese iron pyrophosphate active material, thereby improving the specific capacity, rate performance and cycle stability of the positive electrode material.
[0042] Specifically, in step S4, the mass ratio of the first fumed material to the nitrogen source is 1:(0.01-0.2).
[0043] Preferably, in step S4, the mass ratio of the first fumed material to the nitrogen source is 1:(0.01-0.1).
[0044] More preferably, in step S4, the mass ratio of the first sintered material to the nitrogen source is 1:(0.02-0.04).
[0045] Specifically, the secondary sintering in step S4 is to increase the temperature to 500-650° C. at a heating rate of 1-20° C. / min and keep the temperature for 0.5-10 h.
[0046] The present invention also protects sodium manganese iron pyrophosphate prepared by the above preparation method.
[0047] The present invention also protects the use of the above-mentioned sodium ferromanganese phosphate pyrophosphate in the preparation of sodium ion batteries.
[0048] Compared with the prior art, the present invention has the following beneficial effects:
[0049] The present invention prepares the ammonium ferric manganese phosphate precursor based on the iron process and the ion exchange method, and prepares it into a secondary coated nitrogen-doped carbon-coated sodium ferric manganese phosphate pyrophosphate. The preparation method of the present invention can control the sulfur impurity content in the precursor, avoid the secondary desulfurization process, and make the sulfur impurity content (≤100ppm) in the precursor modified ammonium ferric manganese phosphate reach the battery level, thereby improving the cycle performance of the sodium ion battery.
[0050] The present invention adopts an ion exchange method to effectively control the ratio of the total molar amount of manganese, iron, and doped metal in the ammonium manganese iron phosphate precursor to the molar amount of the phosphorus source to less than 1, greatly improving the tap density of the precursor, facilitating the construction of iron / manganese site defects when preparing sodium manganese iron pyrophosphate, and improving the sodium storage capacity of the positive electrode material. The doped metal elements are evenly distributed at the atomic level in the precursor lattice, effectively controlling the internal crystal electronic structure of sodium manganese iron pyrophosphate, improving the structural stability of sodium manganese iron pyrophosphate, and at the same time alleviating the volume expansion effect of sodium ions during the embedding / de-embedding process.
[0051] The present invention uses a secondary sintering process to uniformly coat the surface of the sodium ferromanganese phosphate pyrophosphate particles with a nitrogen-doped carbon film. The nitrogen-doped carbon film increases the electronic conductivity of the material, improves the wettability of the electrolyte on the surface of the material, provides more sodium ion transmission paths and storage space for the sodium ferromanganese phosphate pyrophosphate active substance, and thus improves the specific capacity, rate performance and cycle stability of the positive electrode material. The secondary sintering process can reduce the content of free carbon in the finished material after pulverization to regulate the uniformity and density of the carbon coating of the material, further inhibit the Jahn-Teller effect caused by manganese dissolution, and increase the crystallinity of the sodium ferromanganese phosphate pyrophosphate particles, thereby optimizing the electrochemical properties and compaction density of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 The battery-grade doped modified NH4Mn prepared in Example 1 0.6 Fe 0.36 Al 0.01 V 0.01 Nb 0.01 Cu 0.01SEM image of PO4 precursor.
[0053] Figure 2 The battery-grade doped modified NH4Mn prepared in Example 2 0.36 Fe 0.6 W 0.01 Mg 0.01 Ti 0.02 SEM image of PO4 precursor. DETAILED DESCRIPTION
[0054] The present invention is further described below in conjunction with examples. These examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually carried out according to conventional conditions in the art or according to the conditions recommended by the manufacturer; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets. Any non-substantial changes and substitutions made by those skilled in the art on the basis of the present invention belong to the scope of protection claimed by the present invention.
[0055] Example 1
[0056] S0. Add 4.4L of ultrapure water to a nitrogen-filled dissolving tank, and dissolve 2.2kg of manganese sulfate monohydrate, 37.1g of anhydrous aluminum sulfate, 57.9g of vanadium oxalate, 116.7g of niobium oxalate, and 34.6g of anhydrous copper sulfate in the above dissolving tank to prepare a mixed metal salt solution Ⅰ;
[0057] S1. Evenly disperse 437.18g of iron powder in a sealed synthetic reactor filled with 10.33L of ultrapure water, introduce nitrogen into the reactor and heat the reactor to 35°C, then slowly pump in 2.52kg of 85wt% concentrated phosphoric acid solution, and stir evenly for 2h to prepare ferrous dihydrogen phosphate solution base liquid II. Slowly heat ferrous dihydrogen phosphate solution base liquid II to 77°C, and slowly pump 1.58kg of 27.5wt% hydrogen peroxide solution into ferrous dihydrogen phosphate solution base liquid II, and after sufficient stirring and reaction for 30min, age for 2h to obtain phosphoric acid-ferric phosphate intermediate system III. First, use ammonia water to adjust the phosphoric acid-ferric phosphate intermediate system III to the intermediate system IV with a pH of 7.
[0058] S2. After slowly pumping the mixed metal salt solution I into the intermediate system IV, the pH of the system was adjusted and stabilized to 7 with ammonia water again, and the system was aged at 77°C for 4 hours under a nitrogen atmosphere to obtain a doped modified ammonium manganese iron phosphate slurry. Finally, the doped modified ammonium manganese iron phosphate slurry was filtered and washed with a vertical filter press until the conductivity of the washing water was 191 μS / cm, and then the filter cake was flash evaporated to obtain a battery-grade doped modified ammonium manganese iron phosphate precursor (NH4Mn 0.6 Fe 0.36 Al 0.01V 0.01 Nb 0.01 Cu 0.01 PO4).
[0059] S3. Doping modified sodium carbonate and battery grade NH4Mn 0.6 Fe 0.36 Al 0.01 V 0.01 Nb 0.01 Cu 0.01 PO4 precursor and sodium dihydrogen phosphate were added into ultrapure water, wherein the molar ratio of Na:(Mn+Fe+Al+V+Nb+Cu):P was 4.02:3:4.02. Polyethylene glycol (the mass of polyethylene glycol was 3wt% of the modified ammonium manganese iron phosphate precursor) was added, and after stirring for 20 minutes, the slurry with a solid content of 32% was transferred into a vertical sand mill for grinding. The grinding particle size D 50 When it is 0.33μm, a spray granulation dryer is used to spray dry the slurry to obtain a spray powder. Subsequently, the aforementioned spray powder is placed in a nitrogen atmosphere box furnace for staged temperature rise sintering. Among them, the temperature is raised to 350℃ at a heating rate of 3℃ / min and kept for 4h, and then the temperature is raised to 550℃ at a heating rate of 3℃ / min and kept for 8h. After naturally cooling to room temperature, the sintered powder obtained from the furnace is air flow crushed and sieved to obtain the battery-grade doped sodium manganese iron pyrophosphate positive electrode material Na4Mn 1.8 Fe 1.08 Al 0.03 V 0.03 Nb 0.03 Cu 0.03 (PO4)2P2O7, the first burning material.
[0060] S4. Place dicyandiamide (the mass of dicyandiamide is 3wt% of the mass of the sinter) at the air inlet end of a nitrogen atmosphere box furnace, and place the first sinter at the air outlet end of a nitrogen atmosphere box furnace, heat it to 550°C at a heating rate of 3°C / min and keep it warm for 1h. After it naturally cools to room temperature, the sintered powder obtained from the furnace is air flow crushed and sieved to obtain a battery-grade doped sodium manganese iron pyrophosphate positive electrode material Na4Mn 1.8 Fe 1.08 Al 0.03 V 0.03 Nb 0.03 Cu 0.03 (PO4)2P2O7 finished product.
[0061] Example 2
[0062] S0. Add 1.5L of ultrapure water to a nitrogen-filled dissolving tank, dissolve 0.79kg of manganese sulfate monohydrate, 38.2g of sodium tungstate, 15.7g of anhydrous magnesium sulfate, and 76.5g of ammonium titanyl oxalate in the above dissolving tank to prepare a mixed metal salt solution Ⅰ;
[0063] S1. Disperse 437.18g of iron powder evenly in a closed synthetic reactor filled with 11.35L of ultrapure water, introduce nitrogen into the reactor and heat the reactor to 38°C, then slowly pump in 1.8kg of 85wt% concentrated phosphoric acid solution, and stir evenly for 2h to prepare ferrous dihydrogen phosphate solution base liquid II. Slowly heat ferrous dihydrogen phosphate solution base liquid II to 77°C, and slowly pump 0.95kg of 27.5wt% hydrogen peroxide solution into ferrous dihydrogen phosphate solution base liquid II, stir and react for 30min, and then age for 2h to obtain phosphoric acid-ferric phosphate intermediate system III. First, use ammonia water to adjust the phosphoric acid-ferric phosphate intermediate system III to an intermediate system IV with a pH of 7.2.
[0064] S2. After slowly pumping the mixed metal salt solution I into the intermediate system IV, the pH of the system was adjusted and stabilized to 7.2 with ammonia water again, and the system was aged at 75°C for 4 hours under a nitrogen atmosphere to obtain a doped modified ammonium manganese iron phosphate slurry. Finally, the doped modified ammonium manganese iron phosphate slurry was filtered and washed with a vertical filter press until the conductivity of the washing water was 189 μS / cm, and then the filter cake was flash evaporated to obtain a battery-grade doped modified ammonium manganese iron phosphate precursor (NH4Mn 0.36 Fe 0.6 W 0.01 Mg 0.01 Ti 0.02 PO4).
[0065] S3. Doping modified sodium carbonate and battery grade NH4Mn 0.36 Fe 0.6 W 0.01 Mg 0.01 Ti 0.02 PO4 precursor and sodium dihydrogen phosphate were added into ultrapure water, wherein the molar ratio of Na:(Mn+Fe+W+Mg+Ti):P was 4.03:3:4.04, and glucose (the mass of glucose was 2wt% of the precursor) was added, and stirred for 20min until the dispersion was uniform. Then the slurry with a solid content of 36% was transferred into a vertical sand mill for grinding. The grinding particle size D 50When it is 0.35μm, a spray granulation dryer is used to spray dry the slurry to obtain a spray powder. Subsequently, the aforementioned spray powder is placed in a nitrogen atmosphere box furnace for staged temperature rise sintering. Among them, the temperature is raised to 380℃ at a heating rate of 3℃ / min and kept for 4h, and then the temperature is raised to 540℃ at a heating rate of 5℃ / min and kept for 9h. After naturally cooling to room temperature, the sintered powder obtained from the furnace is air flow crushed and sieved to obtain the battery-grade doped sodium manganese iron pyrophosphate positive electrode material Na4Mn 1.08 Fe 1.8 W 0.03 Mg 0.03 Ti 0.06 (PO4)2P2O7, the first burning material.
[0066] S4. Place dicyandiamide (the mass of dicyandiamide is 3.6wt% of the mass of the sintered material) at the air inlet end of a nitrogen atmosphere box furnace, and place the first sintered material at the air outlet end of a nitrogen atmosphere box furnace, heat it to 540°C at a heating rate of 3°C / min and keep it warm for 0.5h. After it naturally cools to room temperature, the sintered powder obtained from the furnace is air flow crushed and sieved to obtain a battery-grade doped sodium manganese iron pyrophosphate positive electrode material Na4Mn 1.08 Fe 1.8 W 0.03 Mg 0.03 Ti 0.06 (PO4)2P2O7 finished product.
[0067] Example 3
[0068] S0. Add 2.6L of ultrapure water to a nitrogen-filled dissolving tank, and dissolve 1.16kg of manganese sulfate monohydrate, 37.6g of anhydrous magnesium sulfate, 137.7g of ammonium titanium oxalate, and 41.1g of nickel sulfate hexahydrate in the above dissolving tank to prepare a mixed metal salt solution Ⅰ;
[0069] S1. Evenly disperse 437.18g of iron powder in a sealed synthetic reactor filled with 11.05L of ultrapure water, introduce nitrogen into the reactor and heat the reactor to 40°C, then slowly pump in 1.8kg of 85wt% concentrated phosphoric acid solution, and stir evenly for 2h to prepare ferrous dihydrogen phosphate solution base liquid II. Slowly heat ferrous dihydrogen phosphate solution base liquid II to 77°C, and slowly pump 1.2kg of 27.5wt% hydrogen peroxide solution into ferrous dihydrogen phosphate solution base liquid II, and after sufficient stirring and reaction for 30min, age for 2h to obtain phosphoric acid-ferric phosphate intermediate system III. First, use ammonia water to adjust the phosphoric acid-ferric phosphate intermediate system III to intermediate system IV with a pH of 7.5.
[0070] S2. After slowly pumping the mixed metal salt solution I into the intermediate system IV, the pH of the system was adjusted and stabilized to 7.5 with ammonia water again, and the system was aged at 72°C for 4 hours under a nitrogen atmosphere to obtain a doped modified ammonium manganese iron phosphate slurry. Finally, the doped modified ammonium manganese iron phosphate slurry was filtered and washed with a vertical filter press until the conductivity of the washing water was 197 μS / cm, and then the filter cake was flash evaporated to obtain a battery-grade doped modified ammonium manganese iron phosphate precursor (NH4Mn 0.44 Fe 0.5 Mg 0.02 Ti 0.03 Ni 0.01 PO4).
[0071] S3. Doping modified sodium carbonate and battery grade NH4Mn 0.44 Fe 0.5 Mg 0.02 Ti 0.03 Ni 0.01 PO4 precursor and sodium dihydrogen phosphate were added into ultrapure water, wherein the molar ratio of Na:(Mn+Fe+Mg+Ti+Ni):P was 4.05:3:4.03, and glucose (the mass of glucose was 3.3wt% of the precursor) was added, and stirred for 20min until the dispersion was uniform. Then the slurry with a solid content of 38% was transferred into a vertical sand mill for grinding. The grinding particle size D 50 When it is 0.32μm, use a spray granulation dryer to spray dry the slurry to obtain a spray powder. Subsequently, the aforementioned spray powder is placed in a nitrogen atmosphere box furnace for staged temperature rise sintering. Among them, the temperature is raised to 400℃ at a heating rate of 5℃ / min and kept for 4h, and then the temperature is raised to 600℃ at a heating rate of 3℃ / min and kept for 8h. After naturally cooling to room temperature, the sintered powder obtained from the furnace is air flow crushed and sieved to obtain the battery-grade doped sodium manganese iron phosphate pyrophosphate positive electrode material Na4Mn 1.32 Fe 1.5 Mg 0.06 Ti 0.09 Ni 0.03 (PO4)2P2O7, the first burning material.
[0072] S4. Place melamine (the mass of melamine is 2.2wt% of the mass of the sintered material) at the air inlet end of a nitrogen atmosphere box furnace, and place the first sintered material at the air outlet end of a nitrogen atmosphere box furnace, heat it to 600°C at a heating rate of 3°C / min and keep it warm for 1h. After it naturally cools to room temperature, the sintered powder obtained from the furnace is air flow crushed and sieved to obtain a battery-grade doped sodium manganese iron pyrophosphate positive electrode material Na4Mn 1.32 Fe 1.5 Mg 0.06 Ti 0.09 Ni 0.03(PO4)2P2O7 finished product.
[0073] Comparative Example 1
[0074] This comparative example provides a battery-grade doped sodium manganese iron phosphate pyrophosphate positive electrode material, the chemical formula of which is Na4Mn 1.92 Fe 1.08 (PO4)2P2O7, which is different from Example 1 in that the metal salt solution I contains only monohydrate manganese sulfate, but no aluminum sulfate, vanadium oxalate, niobium oxalate, or anhydrous copper sulfate, the mass of monohydrate manganese sulfate is 2.35 kg, and the conductivity of the wash water is 176 μS / cm. The rest is the same as Example 1.
[0075] Comparative Example 2:
[0076] This comparative example provides a battery-grade doped sodium manganese iron phosphate pyrophosphate positive electrode material, the chemical formula of which is Na4Mn 1.2 Fe 1.8 (PO4)2P2O7, which is different from Example 2 in that the metal salt solution I contains only monohydrated manganese sulfate, but no sodium tungstate, anhydrous magnesium sulfate, or ammonium oxytitanium oxalate, the mass of monohydrated manganese sulfate is 0.88 kg, and the conductivity of the wash water is 159 μS / cm. The rest is the same as Example 2.
[0077] Comparative Example 3
[0078] This comparative example provides a battery-grade doped sodium manganese iron phosphate pyrophosphate positive electrode material, the chemical formula of which is Na4Mn 1.5 Fe 1.5 (PO4)2P2O7, which is different from Example 3 in that the metal salt solution I contains only manganese sulfate monohydrate, but no magnesium sulfate, ammonium titanium oxalate, or nickel sulfate hexahydrate, the mass of manganese sulfate monohydrate is 1.32 kg, and the conductivity of the wash water is 165 μS / cm. The rest is the same as Example 3.
[0079] Comparative Example 4
[0080] S1.1 Add 4.4 L of ultrapure water into a nitrogen-filled dissolving tank, and dissolve 2.2 kg of ferrous sulfate heptahydrate, 2.2 kg of manganese sulfate monohydrate, 37.1 g of anhydrous aluminum sulfate, 57.9 g of vanadium oxalate, 116.7 g of niobium oxalate, and 34.6 g of anhydrous copper sulfate in the above dissolving tank to prepare a mixed metal salt solution I;
[0081] S1.2 Slowly pump 2.52kg of 85wt% concentrated phosphoric acid solution into the closed reactor, introduce nitrogen and heat the reactor to 77°C, then slowly pump the above-mentioned mixed metal salt solution I, use ammonia water to adjust and stabilize the system pH to 7, and place it at 77°C for coprecipitation reaction for 4 hours under a nitrogen atmosphere to obtain a doped modified ammonium manganese iron phosphate slurry. Finally, use a vertical filter press to filter and wash the above-mentioned doped modified ammonium manganese iron phosphate slurry until the conductivity of the washing water is 236μS / cm, and then flash evaporate the filter cake to obtain a doped modified ammonium manganese iron phosphate precursor (NH4Mn 0.6 Fe 0.36 Al 0.01 V 0.01 Nb 0.01 Cu 0.01 PO4).
[0082] S2. Doping sodium carbonate and battery-grade NH4Mn 0.6 Fe 0.36 Al 0.01 V 0.01 Nb 0.01 Cu 0.01 PO4 precursor and sodium dihydrogen phosphate were added into ultrapure water, wherein the molar ratio of Na:(Mn+Fe+Al+V+Nb+Cu):P was 4.02:3:4.02, and polyethylene glycol (the mass of polyethylene glycol was 3wt% of the precursor) was added. After stirring for 20min, the slurry with a solid content of 32% was transferred into a vertical sand mill for grinding. The particle size D 50 When it is 0.33μm, a spray granulation dryer is used to spray dry the slurry to obtain a spray powder. Subsequently, the aforementioned spray powder is placed in a nitrogen atmosphere box furnace for staged temperature rise sintering. Among them, the temperature is raised to 350℃ at a heating rate of 3℃ / min and kept for 4h, and then the temperature is raised to 550℃ at a heating rate of 3℃ / min and kept for 8h. After naturally cooling to room temperature, the sintered powder obtained from the furnace is air flow crushed and sieved to obtain the battery-grade doped sodium manganese iron pyrophosphate positive electrode material Na4Mn 1.8 Fe 1.08 Al 0.03 V 0.03 Nb 0.03 Cu 0.03 (PO4)2P2O7, the first burning material.
[0083] S3. Place dicyandiamide (the mass of dicyandiamide is 3wt% of the mass of the sinter) at the air inlet end of a nitrogen atmosphere box furnace, and place the first sinter at the air outlet end of a nitrogen atmosphere box furnace, heat it to 550°C at a heating rate of 3°C / min and keep it warm for 1h. After it naturally cools to room temperature, the sintered powder obtained from the furnace is air flow crushed and sieved to obtain a battery-grade doped sodium manganese iron pyrophosphate positive electrode material Na4Mn1.8 Fe 1.08 Al 0.03 V 0.03 Nb 0.03 Cu 0.03 (PO4)2P2O7 finished product.
[0084] Comparative Example 5
[0085] S1.1 Add 4.4 L of ultrapure water into a nitrogen-filled dissolving tank, and dissolve 2.2 kg of manganese sulfate monohydrate, 37.1 g of anhydrous aluminum sulfate, 57.9 g of vanadium oxalate, 116.7 g of niobium oxalate, and 34.6 g of anhydrous copper sulfate in the above dissolving tank to prepare a mixed metal salt solution I;
[0086] S1.2 Evenly disperse 437.18g of iron powder in a sealed synthetic reactor containing 10.33L of ultrapure water, introduce nitrogen into the reactor and heat the reactor to 35°C, then slowly pump in 2.52kg of 85wt% concentrated phosphoric acid solution, and stir evenly for 2h to prepare ferrous dihydrogen phosphate solution base liquid II. Slowly heat ferrous dihydrogen phosphate solution base liquid II to 77°C, and slowly pump 1.58kg of 27.5wt% hydrogen peroxide solution into ferrous dihydrogen phosphate solution base liquid II, and age for 2h after sufficient stirring and reaction for 30min to obtain phosphoric acid-iron phosphate intermediate system III. First, adjust the phosphoric acid-iron phosphate intermediate system III to an intermediate system IV with a pH of 7 with ammonia water, then slowly pump the aforementioned mixed metal salt solution I into the intermediate system IV, and then use ammonia water to adjust and stabilize the system pH to 7 again, and place it at 77°C for aging reaction for 4h under a nitrogen atmosphere to obtain a doped modified ammonium manganese iron phosphate slurry. Finally, the doped modified ammonium manganese iron phosphate slurry was filtered and washed with a vertical filter press until the conductivity of the washing water was 191 μS / cm, and then the filter cake was flash evaporated to obtain a battery-grade doped modified ammonium manganese iron phosphate precursor (NH4Mn 0.6 Fe 0.36 Al 0.01 V 0.01 Nb 0.01 Cu 0.01 PO4).
[0087] S2. Doping sodium carbonate and battery-grade NH4Mn 0.6 Fe 0.36 Al 0.01 V 0.01 Nb 0.01 Cu 0.01PO4 precursor and sodium dihydrogen phosphate were added into ultrapure water, wherein the molar ratio of Na:(Mn+Fe+Al+V+Nb+Cu):P was 4.02:3:4.02, and polyethylene glycol (the mass of polyethylene glycol was 3wt% of the precursor) was added. After stirring for 20min, the slurry with a solid content of 32% was transferred into a vertical sand mill for grinding. The particle size D 50 When it is 0.33μm, a spray granulation dryer is used to spray dry the slurry to obtain a spray powder. Subsequently, the aforementioned spray powder is placed in a nitrogen atmosphere box furnace for staged temperature rise sintering. Among them, the temperature is raised to 350℃ at a heating rate of 3℃ / min and kept for 4h, and then the temperature is raised to 550℃ at a heating rate of 3℃ / min and kept for 8h. After naturally cooling to room temperature, the sintered powder obtained from the furnace is air flow crushed and sieved to obtain the battery-grade doped sodium manganese iron pyrophosphate positive electrode material Na4Mn 1.8 Fe 1.08 Al 0.03 V 0.03 Nb 0.03 Cu 0.03 (PO4)2P2O7 finished product.
[0088] Comparative Example 6
[0089] S1.1 Add 4.4 L of ultrapure water into a nitrogen-filled dissolving tank, and dissolve 2.2 kg of manganese sulfate monohydrate, 37.1 g of anhydrous aluminum sulfate, 57.9 g of vanadium oxalate, 116.7 g of niobium oxalate, and 34.6 g of anhydrous copper sulfate in the above dissolving tank to prepare a mixed metal salt solution I;
[0090] S1.2 Evenly disperse 437.18g of iron powder in a sealed synthetic reactor containing 10.33L of ultrapure water, introduce nitrogen into the reactor and heat the reactor to 35°C, then slowly pump in 2.52kg of 85wt% concentrated phosphoric acid solution, and stir evenly for 2h to prepare ferrous dihydrogen phosphate solution base liquid II. Slowly heat ferrous dihydrogen phosphate solution base liquid II to 77°C, and slowly pump 1.58kg of 27.5wt% hydrogen peroxide solution into ferrous dihydrogen phosphate solution base liquid II, and age for 2h after sufficient stirring and reaction for 30min to obtain phosphoric acid-iron phosphate intermediate system III. First, adjust the phosphoric acid-iron phosphate intermediate system III to an intermediate system IV with a pH of 7 with ammonia water, then slowly pump the aforementioned mixed metal salt solution I into the intermediate system IV, and then use ammonia water to adjust and stabilize the system pH to 7 again, and place it at 77°C for aging reaction for 4h under a nitrogen atmosphere to obtain a doped modified ammonium manganese iron phosphate slurry. Finally, the doped modified ammonium manganese iron phosphate slurry was filtered and washed with a vertical filter press until the conductivity of the washing water was 191 μS / cm, and then the filter cake was flash evaporated to obtain a battery-grade doped modified ammonium manganese iron phosphate precursor (NH4Mn 0.6 Fe 0.36 Al0.01 V 0.01 Nb 0.01 Cu 0.01 PO4).
[0091] S2. Doping sodium carbonate and battery-grade NH4Mn 0.6 Fe 0.36 Al 0.01 V 0.01 Nb 0.01 Cu 0.01 PO4 precursor and sodium dihydrogen phosphate were added into ultrapure water, wherein the molar ratio of Na:(Mn+Fe+Al+V+Nb+Cu):P was 4.02:3:4.02, and polyethylene glycol (the mass of polyethylene glycol was 3wt% of the precursor) was added. After stirring for 20min, the slurry with a solid content of 32% was transferred into a vertical sand mill for grinding. The particle size D 50 When it is 0.33μm, a spray granulation dryer is used to spray dry the slurry to obtain a spray powder. Subsequently, the aforementioned spray powder is placed in a nitrogen atmosphere box furnace for staged temperature rise sintering. Among them, the temperature is raised to 350℃ at a heating rate of 3℃ / min and kept for 4h, and then the temperature is raised to 550℃ at a heating rate of 3℃ / min and kept for 8h. After naturally cooling to room temperature, the sintered powder obtained from the furnace is air flow crushed and sieved to obtain the battery-grade doped sodium manganese iron pyrophosphate positive electrode material Na4Mn 1.8 Fe 1.08 Al 0.03 V 0.03 Nb 0.03 Cu 0.03 (PO4)2P2O7, the first burning material.
[0092] S3. The above-mentioned sintered material is placed at the outlet end of a nitrogen atmosphere box furnace, and a carbon source gas (methane, with a ventilation flow rate of 200 mL / min) is introduced into the box furnace, and the temperature is raised to 550°C at a heating rate of 3°C / min and kept for 1 hour. After the temperature naturally drops to room temperature, the sintered powder obtained from the furnace is air flow crushed and sieved to obtain a battery-grade doped sodium manganese iron phosphate pyrophosphate positive electrode material Na4Mn 1.8 Fe 1.08 Al 0.03 V 0.03 Nb 0.03 Cu 0.03 (PO4)2P2O7 finished product.
[0093] Comparative Example 7
[0094] S1. Sodium carbonate, ferrous sulfate heptahydrate, manganese sulfate monohydrate, anhydrous aluminum sulfate, vanadium oxalate, niobium oxalate, anhydrous copper sulfate and sodium dihydrogen phosphate are added to ultrapure water, wherein the molar ratio of Na:(Mn+Fe+Al+V+Nb+Cu):P is 4.02:3:4.02, and the molar ratio of Mn:Fe:Al:V:Nb:Cu is 60:36:1:1:1:1, and polyethylene glycol (the mass of polyethylene glycol is the same as that of Example 1) is added, and after stirring for 20 minutes, the slurry with a solid content of 32% is transferred into a vertical sand mill for grinding, and the ground particle size D 50 When it is 0.33μm, a spray granulation dryer is used to spray dry the slurry to obtain a spray powder. Subsequently, the aforementioned spray powder is placed in a nitrogen atmosphere box furnace for staged temperature rise sintering. Among them, the temperature is raised to 350℃ at a heating rate of 3℃ / min and kept for 4h, and then the temperature is raised to 550℃ at a heating rate of 3℃ / min and kept for 8h. After naturally cooling to room temperature, the sintered powder obtained from the furnace is air flow crushed and sieved to obtain the battery-grade doped sodium manganese iron pyrophosphate positive electrode material Na4Mn 1.8 Fe 1.08 Al 0.0 3V 0.03 Nb 0.03 Cu 0.03 (PO4)2P2O7, the first burning material.
[0095] S2. Place dicyandiamide (the mass of dicyandiamide is 3wt% of the mass of the sinter) at the air inlet end of a nitrogen atmosphere box furnace, and place the first sinter at the air outlet end of a nitrogen atmosphere box furnace, heat it to 550°C at a heating rate of 3°C / min and keep it warm for 1h. After it naturally cools to room temperature, the sintered powder obtained from the furnace is air flow crushed and sieved to obtain a battery-grade doped sodium manganese iron pyrophosphate positive electrode material Na4Mn 1.8 Fe 1.08 Al 0.03 V 0.03 Nb 0.03 Cu 0.03 (PO4)2P2O7 finished product.
[0096] Test Method
[0097] The prepared materials were tested for sulfur content, manganese content and doping element content using inductively coupled plasma testing method.
[0098] The iron content of the prepared material was tested by potassium dichromate titration method; the phosphorus content of the prepared material was tested by quinoline molybdate precipitation weight method.
[0099] A powder compaction density meter is used to apply a specific pressure to the prepared material and measure its volume and mass to obtain the compaction density of the sample.
[0100] The prepared finished material was used as the positive electrode active material, and the active material: conductive agent carbon black: binder polyvinylidene fluoride was weighed and dispersed in N-methylpyrrolidone dispersant according to the mass ratio of 92:4:4 to form a uniformly dispersed positive electrode slurry, which was then coated on a carbon-coated aluminum foil and vacuum dried at 105°C for 10 hours, and then punched and weighed to obtain a round phosphate pyrophosphate manganese iron sodium ion battery electrode. Using a metal sodium sheet as the negative electrode, the prepared electrode as the positive electrode, glass fiber as the separator, and 1 mol / L NaClO4 solution (DMC:EC=1:1Vol%) as the electrolyte, a 2032 type sodium ion button battery was assembled in an inert atmosphere glove box, and related electrochemical performance tests were performed.
[0101] Scanning electron microscope (SEM) test results are as follows Figure 1 and 2 As shown, Figure 1 The battery-grade doped modified NH4Mn prepared in Example 1 0.6 Fe 0.36 Al 0.01 V 0.01 Nb 0.01 Cu 0.01 PO4 precursor, Figure 2 The battery-grade doped modified NH4Mn prepared in Example 2 0.36 Fe 0.6 W 0.01 Mg 0.01 Ti 0.02 PO4 precursor. As can be seen from the figure, the first precursor is a micron-sized cluster structure composed of nano-sheets.
[0102] The physicochemical index test data of the ammonium manganese iron phosphate precursor of the embodiment of the present invention and the comparative example are shown in Table 1.
[0103] Table 1
[0104]
[0105]
[0106] As shown in Table 1, the sulfur content of the ammonium manganese iron phosphate precursor prepared in Examples 1-3 is less than 100ppm, reaching the level of sodium positive electrode materials, which can effectively avoid the side reaction of sulfur impurities with the electrolyte during the cycle to produce sulfur-containing byproducts and affect the cycle stability of the battery. At the same time, the n(Mn):n(Fe) measured in the ammonium manganese iron phosphate precursor is consistent with the design value, indicating that the simple synthesis method proposed in the present invention of first preparing the iron phosphate template by imitating the iron method and then using the ion exchange principle to dope and modify the ammonium manganese iron phosphate is effective. In addition, the process can control n(Mn+Fe+M):n(P) in the precursor to be less than 1. When it is used as a precursor to synthesize sodium manganese iron phosphate pyrophosphate, it can effectively regulate the vacancies of metal manganese and iron in the bulk phase, which is conducive to accelerating the migration of sodium ions and alleviating the volume expansion effect of the material, thereby improving the electrochemical performance of the positive electrode material. Compared with Comparative Examples 1-3, the introduction of metal doping elements in the ammonium manganese iron phosphate precursor prepared in Examples 1-3 did not affect the sulfur impurity content, the main element n(Mn):n(Fe) ratio, and the n(Mn+Fe+M):n(P) ratio, indicating that the preparation method of the present invention for doping modification and forming a manganese iron solid solution by ion exchange is highly effective. It can be seen from Comparative Example 4 that the sulfur impurity content in the precursor prepared by the coprecipitation method is too high and n(Mn+Fe+M):n(P)>1 in the precursor. In addition, in Comparative Example 7, the sulfur impurity content of sodium manganese iron phosphate pyrophosphate prepared by direct mixing, grinding, spraying, and sintering of manganese salt, iron salt, sodium source, phosphorus source, and carbon source reached 4261ppm, far exceeding Examples 1-3 of the present invention, indicating that the technical route of direct mixing of sulfates cannot prepare sodium manganese iron phosphate pyrophosphate with low sulfur impurity content.
[0107] The physicochemical index test data of the sodium ferromanganese phosphate pyrophosphate prepared in the examples of the present invention and the comparative examples are shown in Table 2:
[0108] Table 2
[0109]
[0110]
[0111] As shown in Table 2, the use of modified ammonium manganese iron phosphate precursor with high tap density and n(Mn+Fe+M):n(P)<1 in Examples 1-3 greatly improves the compaction density of sodium manganese iron phosphate pyrophosphate. Compared with Comparative Examples 1-3, the specific metal doping modification strategy makes the primary particles of Examples 1-3 present a better size gradation during the sintering process, which improves the compaction density of the material; at the same time, the uniform bulk doping effectively improves the sodium storage capacity and cycle stability of the material, so that the capacity retention rate of Examples 1-3 after 100 cycles at 1C rate is better.
[0112] It can be seen from Example 1 and Comparative Example 5 that Example 1 is based on a chemical vapor deposition-like method through a secondary sintering process (CVD, using a solid nitrogen carbon source, etc. to decompose gas at a certain temperature for chemical vapor deposition film formation) to uniformly coat the surface of the sodium ferromanganese phosphate pyrophosphate particles with a nitrogen-doped carbon film, reducing the content of free carbon in the finished material after crushing, effectively regulating the uniformity and density of the carbon coating in the material, thereby improving the conductivity and structural stability of the material, inhibiting manganese dissolution and the Jahn-Teller effect, and effectively improving the electrochemical performance of the sodium ferromanganese phosphate pyrophosphate. In addition, the crystallinity of the sodium ferromanganese phosphate pyrophosphate particles can be effectively optimized through secondary sintering, thereby improving the electrochemical performance and compaction density of the material, which is conducive to the preparation of a sodium ferromanganese phosphate pyrophosphate positive electrode material with a high compaction density.
[0113] It can be seen from Example 1 and Comparative Example 6 that in Example 1, a solid nitrogen carbon source is used to replace the conventional carbon source gas on the surface of the sodium manganese iron phosphate pyrophosphate-burned material based on a chemical vapor deposition method, and nitrogen atoms are effectively doped and defect sites are constructed in the secondary coated carbon layer. Nitrogen atoms have similar atomic radii to carbon atoms. As doping atoms (pyrrolic nitrogen and pyridinic nitrogen) in the carbon film, they have better electron affinity, can provide lone pairs of electrons and contribute free electrons to regulate the local charge distribution and electron cloud structure in the carbon film, improve the electronic conductivity of the material and improve the wettability of the electrolyte on the surface of the material, and promote the transmission of electrons and sodium ions; at the same time, nitrogen atom doping can construct defect sites, providing more sodium ion transmission paths and storage space for the sodium manganese iron pyrophosphate active material, thereby improving the specific capacity, rate performance and cycle stability of the positive electrode material.
[0114] It can be seen from Example 1 and Comparative Examples 4 and 7 that the compaction density of the material decreases due to the precursor n(Mn+Fe+M):n(P)>1 in Comparative Example 4; and the excessively high sulfur content in the prepared finished product will directly affect the sodium storage capacity and cycle stability of the material, so that the capacity retention rates of Comparative Examples 4 and 7 after 100 cycles at a 1C rate are not as good as those of the other embodiments and comparative examples in the present invention.
[0115] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing sodium ferromanganese phosphate pyrophosphate, characterized in that: The following steps are involved: S1. The elemental iron is placed in phosphoric acid for reaction, an oxidant is added for reaction, and an alkaline pH regulator containing nitrogen is added to obtain a first system containing ammonium iron phosphate; S2. mixing manganese sulfate and a doping metal salt, adding the mixture to a first system containing ammonium ferric phosphate, and reacting the mixture under an inert atmosphere to obtain a first precursor; S3. The first precursor is mixed with a sodium source, a phosphorus source, and a carbon source, ground, spray dried, and sintered in an inert atmosphere to obtain a first sintered material; S4. The first sintered material is secondarily sintered in a mixed atmosphere of an inert gas and a gaseous nitrogen source to obtain the sodium ferromanganese phosphate pyrophosphate.
2. The preparation method according to claim 1, characterized in that: The chemical formula of the sodium manganese iron pyrophosphate is Na4Mn α Fe 3-α-β M β (PO4)2P2O7, 0<α<3, 0<β<0.3, M is the doping metal.
3. The preparation method according to claim 1, characterized in that: The molar ratio of the elemental iron to the phosphoric acid is 1:(2-5).
4. The preparation method according to claim 1, characterized in that: The doping metal is at least one of Al, Ti, V, Ca, Ce, Cu, Cr, Zr, Sr, Ni, Co, Zn, Sn, Nb, Na, Mo, Mg, W, and La.
5. The preparation method according to claim 1, characterized in that: The ratio of the total molar number of manganese, iron and doping metal to the molar number of phosphorus in the first precursor is less than 1.
6. The preparation method according to claim 1, characterized in that: In the step S3, the carbon source is 0.05-5 wt % of the mass of the first precursor.
7. The preparation method according to claim 1, characterized in that: The nitrogen source is at least one of urea, dicyandiamide, melamine, thiourea and cyanamide.
8. The preparation method according to claim 1, characterized in that: In the step S4, the mass ratio of the first sintered material to the nitrogen source is 1:(0.01-0.2).
9. Sodium manganese iron pyrophosphate prepared by the preparation method according to any one of claims 1 to 8.
10. Use of sodium manganese iron pyrophosphate as claimed in claim 9 in the preparation of sodium ion batteries.
Citation Information
Cited By
Carbon-coated ion-doped ferric sodium pyrophosphate positive electrode material and preparation method thereof
CN120440863A
Positive electrode material and preparation method thereof, battery and electric equipment
CN120545360A
Method for preparing manganese iron vanadium sodium phosphate by recovering lithium manganese iron phosphate
CN120817587A